ANALISIS HUBUNGAN TUNJANGAN PROFESI GURU DAN UJIAN NASIONAL - Adhi Prasetyo Wibowo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
The teacher professional allowance (TPG) is expected to improve the quality of national education which refers to the National Education Standards (SNP) especially the graduation competency standards. The TPG budget tends to increase every year, but graduation competency standards tend to decrease. Therefore, this study aims to determine the relationship of teacher professional allowance and national examinations. The data used are secondary data consisting of TPG budget and UN results. Teacher professional allowance budget from 2012-2018. Whereas the UN score used is the average national aggregate UN score from 2012-12018. While the model used is the person and spearman correlation test. The results showed that the relationship between TPG and UN had a positive direction, but it was not significant.